Incarcerated femoral hernia containing ovary and fallopian tube in a 54-year-old. (5th August 2011) - Coyle, David; Kavanagh, Nora; Mahmoud, Akthar; Lowery, Aoife J.; Khan, Waqar; Barry, Kevin
Abstract : While accounting for a small proportion of groin hernias, femoral hernias have the greatest propensity to incarcerate and strangulate leading to significant morbidity and mortality. The authors present a case of a 54-year-old multiparous female presenting with a new firm painful left-sided groin lump for 1 day. Incarcerated femoral hernia was diagnosed clinically and open surgical repair was undertaken. At surgery a viable ovary and fallopian tube were found in the hernial sac and returned to the pelvis. This case emphasises the importance of awareness of the variety of pathologies that may be encountered in emergency hernia surgery and highlights the value of preoperative radiology in such cases.